Technology and knowledge transfers in production networks: Case study on Philippine food manufacturing firms - Fatima Lourdes Del Prado; Maureen Ane D. Rosellon (Philippine Institute for Development Studies (PIDS), 2017)
This paper investigates firm-to-firm technology and knowledge sharing in firms from the food manufacturing sector. Traditionally driven by secret recipes and family-grounded procedures, food processing firms are naturally unwilling and indisposed to embrace collaborative undertaking and develop external ties due to perceived risks of leakage of company specific assets. This paper attempts to document the practical experiences of two manufacturing firms and their views on sharing technology and knowledge to their partners in the production network.
Keywords: 330; technology transfer; knowledge transfer; production networks; knowledge sharing; food manufacturing